Regulation of granuloma fibrosis by nitric oxide during Mycobacterium avium experimental infection - Susana Lousada (2006)
Collagen deposition within granulomas formed after Mycobacterium avium infection was analysed on histological sections stained with Masson's trichrome using acquired computerized image analysis and a program that was specifically designed for that purpose. Comparison was made between immunocompetent C57BL/6 mice and mice genetically deficient in the inducible nitric oxide (NO) synthase gene (iNOS(-/-) mice) infected with either a highly virulent strain or a moderately virulent strain of M. avium. iNOS-deficient mice were more resistant to the highly virulent strain than control C57B1/6 mice, but both strains were equally susceptible to the less virulent M. avium strain. Collagen distribution in the granuloma was found in the cuff surrounding the granuloma in an area rich in lymphoid cells as well as inside the granuloma itself, conferring a mesh-like structure within that lesion. It was seen that iNOS(-/-) mice induced a higher collagen deposition than C57BL/6 mice and that such collagen deposition varied with the mycobacterial strain used to infect the animals.